2009
DOI: 10.1007/s10508-009-9585-4
|View full text |Cite
|
Sign up to set email alerts
|

Viewing Sexually-Explicit Materials Alone or Together: Associations with Relationship Quality

Abstract: This study investigated associations between viewing sexually-explicit material (SEM) and relationship functioning in a random sample of 1291 unmarried individuals in romantic relationships. More men (76.8%) than women (31.6%) reported that they viewed SEM on their own, but nearly half of both men and women reported sometimes viewing SEM with their partner (44.8%). Measures of communication, relationship adjustment, commitment, sexual satisfaction, and infidelity were examined. Individuals who never viewed SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
145
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 185 publications
(156 citation statements)
references
References 26 publications
8
145
0
3
Order By: Relevance
“…This difference must be emphasized. Other studies have also shown that women's use of pornography may be beneficial to their sexual satisfaction [1] [11]. These results suggest that women satisfy their sexual desires and fantasies through pornography.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…This difference must be emphasized. Other studies have also shown that women's use of pornography may be beneficial to their sexual satisfaction [1] [11]. These results suggest that women satisfy their sexual desires and fantasies through pornography.…”
Section: Discussionmentioning
confidence: 64%
“…Research has shown that visiting sexually explicit sites is associated with a greater likelihood of infidelity [1] [5], especially in men during their first years of marriage [5]. In a study by Stack, Wasserman, and Kern [46], adults who had used pornography more than three times in the last month were more likely to be unfaithful than adults who did not report extradyadic sexual behaviors.…”
Section: Pornography and Infidelitymentioning
confidence: 99%
See 3 more Smart Citations